Desenvolvendo jogos educativos para o ensino de física : um material didático alternativo de apoio ao binômio ensino-aprendizagem - Pereira, Ricardo Francisco (2008)
In the actual learning-teaching process, from Fundamental level until the University schools, the educators, many time, are unsuccessfully to awake the interest of their students. The traditional approaches of education are less and less attractive for the students. Many times, the educators don't create fields of real participation of the students in the classrooms. These are transformed in an immense space of "anticreation" places. The present project intends to discuss the return of the ludicity, through the comprehension of the present situation of the Physics education, designing educational games that set out the main difficulties found by the students. Positive and negative points of this approach will be mapped involving Physics teachers. This alternative approach will be contextualized on the needs of the teachers and of their students, wanting to transform it in a powerful pedagogical practice. With the approach of specific contents in the games, is possible a deep involvement and participation of the students, when is created a playful environment to develop the learning-teaching process on Physics contents. Games involving the participation of Physics teachers will be analyzed, especially their speechs under a phenomenological analisis.